Pengaruh Gaya Kepemimpinan, Pengawasan dan Motivasi Kerja terhadap Disiplin Kerja Karyawan PT. Media Sarana Data - Suryandari,, Marul; Linawati, Linawati; Sofiati, Sofiati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the influence of leadership style, supervision and work motivation on employee work discipline at PT Media Sarana Data. The sample used in this study consisted of 69 respondents. Data collection was carried out by distributing questionnaires to respondents. Multiple linear regression method is used to analyze in this study. This study shows the results that leadership style has no positive effect on work discipline with a t value of -1.088 <1.996 (t table) and a significance value of t is 0.281 > 0.05, so the first hypothesis (H1) in this study is not accepted. Supervision has a positive effect on work discipline with a t value of 4.040 > 1.966 (t table) and a significance value of t 0.000 <0.05, so the second hypothesis (H2) of this study is accepted. Work motivation has a positive effect on work discipline with a t count of 3.002 > 1.966 (t table) and a significance value of t 0.004 <0.05, so the third hypothesis (H3) of this study is accepted. Keywords: Leadership Style, Supervision, Work Motivation, Work Discipline